EXTREM SPORT, A QUALITATIVE RESEARCH (GYMNASIUM, 2009)
The purpose of this study was to try to grow the understanding of the meanings and motivationsassociated with involvement in extreme sport. Since extreme sport is a relatively recent phenomenon, not somany psychological research in this area has been carried out. The sample of participants was composed ofsix athletes participated in two extreme sports.We adopted qualitative research methodologies in order to access meanings and motivationsassociated with extreme sports. Conclusions: participants in extreme sport are searching more than thrillsand excitement, it is a deliberate and self-conscious approach to the activity, making informed choices ratherthan simply acting out unresolved conflicts or implementing distorted cognition.